PENGARUH DEBT COVENANT DAN INTENSITAS MODAL TERHADAP KONSERVATISME AKUNTANSI - FARADILA, AISYAH; ATIKAH, SITI (GANEC SWARA, 2024)
The purpose of this study was to analyze the effect of debt covenants and capital intensity on accounting conservatism in transportation and logistics companies in Indonesia in the span of 2018-2022. The total sampling method is used using 50 companies listed on the Indonesia Stock Exchange (IDX) as a sample. This study uses secondary data obtained from the Indonesia Stock Exchange (IDX) and the Osiris data center of the Faculty of Economics and Business, Mataram University. The results showed that Debt Covenant had no negative effect on accounting conservatism, while capital intensity had a significant positive effect on accounting conservatism. These findings can help managers and stakeholders in understanding the factors that influence accounting conservatism in transportation and logistics companies. Suggestions for further researchers to expand the scope of the sample and add other factors that affect accounting conservatism